2019
DOI: 10.1101/808394
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

When two are better than one: Modeling the mechanisms of antibody mixtures

Abstract: AbstractIt is difficult to predict how antibodies will behave when mixed together, even after each has been independently characterized. Here, we present a statistical mechanical model for the activity of antibody mixtures that accounts for whether pairs of antibodies bind to distinct or overlapping epitopes. This model requires measuring n individual antibodies and their Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Second, the calculator assumes the neutralizing activity of human polyclonal serum is represented by an equipotent mix of the monoclonal antibodies that happen to have been previously characterized by deep mutational scanning. Third, the calculator simply averages site-level escape measurements across antibodies, and does not yet implement a real biophysical model of the combined activity of multiple antibodies (Einav and Bloom 2020). Finally, and in our minds most significantly, the calculator estimates the impact of mutations in reference to antibodies targeted to the early Wuhan-Hu-1 RBD-an approach that is currently reasonable, but will become problematic as human exposure and vaccination histories diversify in the years to come (see last paragraph).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the calculator assumes the neutralizing activity of human polyclonal serum is represented by an equipotent mix of the monoclonal antibodies that happen to have been previously characterized by deep mutational scanning. Third, the calculator simply averages site-level escape measurements across antibodies, and does not yet implement a real biophysical model of the combined activity of multiple antibodies (Einav and Bloom 2020). Finally, and in our minds most significantly, the calculator estimates the impact of mutations in reference to antibodies targeted to the early Wuhan-Hu-1 RBD-an approach that is currently reasonable, but will become problematic as human exposure and vaccination histories diversify in the years to come (see last paragraph).…”
Section: Discussionmentioning
confidence: 99%
“…We report here the first use of quantitative analyses of drug synergy for preclinical and clinical development of a therapeutic antibody cocktail. These analyses build on a general framework for evaluating the effects of multiple drugs acting on a single target that was initially developed to model enzyme inhibition 55 . In that context it was shown that mutually exclusive inhibitors (i.e., competitive) have an additive inhibitory effect, whereas mutually nonexclusive inhibitors (i.e., independent) have a multiplicative (i.e., synergistic) effect.…”
Section: Discussionmentioning
confidence: 99%
“…In that context it was shown that mutually exclusive inhibitors (i.e., competitive) have an additive inhibitory effect, whereas mutually nonexclusive inhibitors (i.e., independent) have a multiplicative (i.e., synergistic) effect. This framework can be applied more generally, for example to antibody inhibitors of a protein 56 , and has the potential to inform decisions around drug cocktail formulation, including selection of lead candidates and optimization of their relative concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…And yet, polyclonal responses cannot be fully explained by monoclonal binding, at least in part due to two factors. First, Abs present in a mixture do not behave additively ( Zwick et al., 2001 ; Ndifon et al., 2009 ; Koefoed et al., 2011 ; Luo and Perelson, 2015 ; Derking et al., 2015 ; Howell et al., 2017 ; Caskey et al., 2019 ; Einav and Bloom, 2020 ; Greiff et al., 2012 ; Bachmann et al., 1997) . Second, seemingly passive Abs can influence ongoing selection of B cells during affinity maturation ( Ng et al., 2010 ; Zhang et al., 2013 ; Schoofs et al., 2016 ; Vono et al., 2019 ; Garg et al., 2019) .…”
Section: Introductionmentioning
confidence: 99%